2018
DOI: 10.1371/journal.pone.0208732
|View full text |Cite
|
Sign up to set email alerts
|

Improved growth of pea, lettuce, and radish plants using the slow release of hydrogen sulfide from GYY-4137

Abstract: Hydrogen sulfide (H2S) is a key gasotransmitter in agriculture and has been reported to increase the growth of plants in the first two weeks and to mitigate the effects of environmental stressors. GYY-4137 is widely used in these studies because it slowly releases H2S, but there is disagreement as to whether it requires enzymes to release H2S. In this article we describe the release of H2S in water without enzymes and that it releases H2S faster in organic solvents than in water or when mixed in topsoil. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 55 publications
2
23
1
Order By: Relevance
“… 2 , 11 22 , 52 GYY-4137 was shown to increase the harvest yield of lettuce and radishes when grown from seeds to harvest in less than six weeks. 14 This work was completed in a greenhouse with plants individually planted in growing pots. In an outdoor trial using corn grown individually in potting containers, dibutyldithiophosphate was shown to increase the weight of corn stalks when it was added to the seed at planting and the corn plants were harvested after 4.5 weeks.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 11 22 , 52 GYY-4137 was shown to increase the harvest yield of lettuce and radishes when grown from seeds to harvest in less than six weeks. 14 This work was completed in a greenhouse with plants individually planted in growing pots. In an outdoor trial using corn grown individually in potting containers, dibutyldithiophosphate was shown to increase the weight of corn stalks when it was added to the seed at planting and the corn plants were harvested after 4.5 weeks.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In recent work, we showed that milligram loadings of GYY-4137 and dibutyldithiophosphate increased the harvest yields of radishes ( Raphanus sativus ), peas, and lettuce and increased the growth of corn plants. 11 , 14 The mechanism for how H 2 S has an important effect on plants is poorly understood, although it is likely that it acts on plant enzymes similar to how it has been shown to act on enzymes in human cells. 4 , 7 10 The application of exogenous H 2 S in agriculture is a new and potentially useful target to promote the survival of plants in a changing climate and to improve the harvest yields of many crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Although the structure and complexity of such systems have evolved signicantly, an early and broadly-used example of such donors is the hydrolysisactivated donor GYY4137, which relies on the hydrolytic cleavage of P]S bonds to generate H 2 S. 27 GYY4137 has been used in >200 publications to date (Web of Science) and exhibits anti-inammatory, vasorelaxant, and anti-cancer as well as other effects in different biological models [27][28][29] with diverse applications ranging from medicinal to agricultural science. 30,31 Motivated by the broad utility of this approach to access H 2 S donor motifs, we sought to use similar chemistry to generate well-dened H 2 Se donors that are activated by P]Se bond hydrolysis. To prepare such a donor, we treated Woollins' reagent with an excess of morpholine, drawing parallels to the synthesis of GYY4137, to generate TDN1042 in moderate yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Their solutions are easy to prepare and apply; however, release of gaseous H 2 S to the atmosphere is quite fast. Recently, slow-release donor GYY-4137 (P-(4-methoxyphenyl)-P-4-morpholinyl-phosphinodithioic acid), which releases H 2 S as a result of hydrolysis (and probably also in an enzymatic way) in a prolonged time period, was found to be more convenient to handle and experiment on plants [ 103 ]. There are no reports on its effect during metallic stress, but these are expected in the near future.…”
Section: Major Players In Chemical Priming Towards Toxic Metal(loid) Tolerancementioning
confidence: 99%